GAMBARAN ACCEPTANCE OF DATING VIOLENCE PADA DEWASA AWAL YANG MENJADI KORBAN KEKERASAN DALAM PACARAN - Ari Pratiwi; Ayu Septi P (MANASA, 2020)
This study aims to determine how the description of acceptance of dating violence in victims ofdating violence. The description described concerns how the attitude and behavior of the victimin acceptance of dating violence and the factors that influence it. The method used in thisresearch is a qualitative method with a phenomenological approach. The technique of selectingparticipants using purposive sampling technique. Participants in this study were 4 people, aged20-25 years and currently experiencing dating violence. The data collection technique usedwas the interview technique, while the analysis technique used to process the data was theMiles and Huberman analysis technique. The results of the study reveal that Acceptance ofdating violence occurs through 2 different processes. The first process involves putting up afight before giving rise to acceptance of dating violence. The second process is to do nothingor surrender and immediately generate acceptance of dating violence. This process is basedon factors, namely shackling affections, feelings of helplessness, limitations in understandingproblems, expectations of protective figures, pre-married sex, views of family and other people,and views of relationships (commitment, duration of relationship, and sense of responsibility)